2014
DOI: 10.15407/ubj86.06.106
|View full text |Cite
|
Sign up to set email alerts
|

Functional and dynamic state of inner mitochondrial membrane of sarcoma 37 in mice under administration of sodium dichloroacetate

Abstract: the activity of enzymes of the respiratory chain and structural-dynamic properties of the inner mitochondrial membrane (IMM) of sarcoma 37 (S37) in mice under sodium dichloroacetate (SDa) administration in a daily dose of 86 mg/kg of body weight starting from the 2 nd day after tumor transplantation were investigated. The dynamic and structural state of the IMM components was determined using the fluorescent probes. With S37 growth the intensification of glycolytic metabolism occurred on the background of supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
1
0
3
Order By: Relevance
“…A similar mechanism of SDA action, increasing mitochondrial metabolism and ROS production under mitochondrial dysfunction is specific for many malignant tumors, which energy metabolism, as known, is characterized by the Warburg effect against the background of the mitochondrial structure-functional disorders [6]. In our previous studies, the cytotoxic action of SDA was observed only in transplanted sarcoma 37, but not in Lewis lung carcinoma, as a possible result of the biological properties of tumors, characteristics and extent of energy metabolism reprogramming, structural and functional abnormalities of the mitochondrial membranes and prooxidant-antioxidant homeostasis impairment [6,36,37].…”
Section: Fig 3 the Influence Of The 1 MM Sodium Nitroprusside (Snp)mentioning
confidence: 99%
“…A similar mechanism of SDA action, increasing mitochondrial metabolism and ROS production under mitochondrial dysfunction is specific for many malignant tumors, which energy metabolism, as known, is characterized by the Warburg effect against the background of the mitochondrial structure-functional disorders [6]. In our previous studies, the cytotoxic action of SDA was observed only in transplanted sarcoma 37, but not in Lewis lung carcinoma, as a possible result of the biological properties of tumors, characteristics and extent of energy metabolism reprogramming, structural and functional abnormalities of the mitochondrial membranes and prooxidant-antioxidant homeostasis impairment [6,36,37].…”
Section: Fig 3 the Influence Of The 1 MM Sodium Nitroprusside (Snp)mentioning
confidence: 99%
“…В связи с этим проведены исследования энергетического метаболизма и окислительных процессов в клетках перевиваемых опухолей мышей разного гистологического генеза -саркомы 37 (С37) и карциномы легкого льюис (Клл) в кинетике роста in vivo и при воздействии ДХАН [115][116][117][118][119]. Установлено торможение роста опухоли и увеличение средней продолжительности жизни при введении ДХАН мышам с С37, но не Клл.…”
Section: модификация функционирования митохондрий опухолевых клеток дunclassified
“…В результате проведенных исследований выявлено, что стационарная фаза роста С37 характеризуется увеличением содержания лактата в опухоли, угнетением функциональной актив-ности комплексов дыхательной цепи митохондрий опухолей, что не выявлено для Клл. При введении ДХАН мышам с С37 в опухоли увеличивается активность пируватдегидрогеназы и происходит снижение содержания лактата, а также уменьшается активность энзимов дыхательной цепи и снижается содержание цитохромов во ВММ [117]. Наряду с этим имеют место конформационные перестройки протеиновых молекул и изменение структурной упорядоченности липидной фазы ВММ, снижение в ней содержания общих липидов и фосфолипидов [115,117].…”
Section: модификация функционирования митохондрий опухолевых клеток дunclassified
See 1 more Smart Citation